2016
DOI: 10.1038/onc.2016.344
|View full text |Cite
|
Sign up to set email alerts
|

HDAC1 and HDAC2 integrate the expression of p53 mutants in pancreatic cancer

Abstract: Mutation of p53 is a frequent genetic lesion in pancreatic cancer being an unmet clinical challenge. Mutants of p53 have lost the tumour-suppressive functions of wild type p53. In addition, p53 mutants exert tumour-promoting functions, qualifying them as important therapeutic targets. Here, we show that the class I histone deacetylases HDAC1 and HDAC2 contribute to maintain the expression of p53 mutants in human and genetically defined murine pancreatic cancer cells. Our data reveal that the inhibition of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 82 publications
4
65
0
2
Order By: Relevance
“…Previous studies suggested that upregulated MRGBP might promote proliferation of colorectal cancer cells through the regulation of BRD8 . Furthermore, MRGBP could regulate stability and/or synthesis of both TIP60/HAT complex and HDACs complexes, which are associated with tumor occurrence and advance, as well as aggressive biological behaviors . We previously revealed that MRGBP expression was significantly upregulated in PanCa samples and cell lines .…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies suggested that upregulated MRGBP might promote proliferation of colorectal cancer cells through the regulation of BRD8 . Furthermore, MRGBP could regulate stability and/or synthesis of both TIP60/HAT complex and HDACs complexes, which are associated with tumor occurrence and advance, as well as aggressive biological behaviors . We previously revealed that MRGBP expression was significantly upregulated in PanCa samples and cell lines .…”
Section: Discussionmentioning
confidence: 94%
“…It is clear that both histone acetylation and deacetylation affect chromatin remodeling as strong epigenetic mechanisms. Interestingly, evidence from several reports indicates that HDAC levels are increased in certain cancer types (22)(23)(24). In addition, HDAC inhibitors have been reported to enhance the acetylation of histones, in tumor cells (25).…”
Section: Hdac Inhibitors As Anti-cancer Agentsmentioning
confidence: 99%
“…HDAC inhibitors have a potent role in cancer pathogenesis and progression. A number of reports indicate that in certain types of cancer, HDAC levels are increased (21)(22)(23)(24).…”
Section: Hdac Inhibitors As Anti-breast Cancer Agentsmentioning
confidence: 99%